PENGARUH WORD OF MOUTH DAN ATRIBUT PRODUK TERHADAP MINAT BELI KONSUMEN PADA HELM NHK MASYARAKAT KECAMATAN ULOK KUPAI - Rahmat Zakaria (Yayasan Insani Mandiri Santani, 2020)
This research is based on the importance of using a helmet for motorcycle riders. The formulation of problem of this research is whether word of mouth (X1) and product attributes (X2) have a partial and simultaneous effect on consumer buying interest (Y). The purpose of research is to test and analyze the effect of word of mouth (X1) and product attributes (X2) on consumers buying interest (Y) on NHK helmets at Ulok Kupai District, Bengkulu Utara regency.Object of this research was the Ulok Kupai Subdistrict Society, Bengkulu Utara with an accidental sampling method. The stduy involved 70 respondents from the member of the society. The data were collected trough field research, observation, and questionnaires. The data collected then was analyzed by using classic assumptions test, multiple linear regression analysis, and hypothesis testing.Based on the multiple linear regression tests using SPSS, the result of the study show that Y = 3.365 + 0.464X1+ 0.279X2. The results of the analysis found that word of mouth (X1) has a positive effect on consumer buying interest (Y). In addition, product attributes (X2)also had a positive effect on consumer buying interest (Y). The result of T test and F test shows that the two variables had a significant effect on consumer buying interest with a significance level of <0.05. This means that Ho is rejected Ha accepted.